ҚИШЛОҚ ХЎЖАЛИГИНИ ИХТИСОСЛАШТИРИШНИНГ ИЛМИЙ АСОСЛАРИ - Ешимбетов, У.Х.; Сарсенбаев, Қ.А. (SCIENCE and SOCIETY, 2023)
The article is devoted to the theoretical foundations of agricultural specialization. It is emphasized that specialization is the guarantee of increasing production efficiency.
Keywords: material production; labor distribution; specialization; labor cooperation; concentration; intensive development